Réforme des tribunaux administratifs et contrôle judiciaire: les inconsistances et les hésitations du Rapport Ouellette - Garant, Patrice (Les Cahiers de droit, 1988)
Are privative clauses useless in contemporaneous Administrative Law ? That is what the Report of Groupe de travail sur les tribunaux administratifs presided by professor Yves Ouellette appears to assume when it recommends their abolishment to Quebec legislators. Privative clauses are statutory protection given to administrative tribunals against any judicial interference, except in the cases of want or excess of juridiction. Since the Alliance case in 1953 it has been held that superior courts cannot be deprived of their supervisory jurisdiction on jurisdictional errors of law or fact ; a full privative clause would even be unconstitutional since Crevier in 1982. More recently, in New Brunswick Liquor Corporation and in Control Data, the Supreme Court specified that jurisdictional control extends to pattently unreasonable intrajurisdictional errors of law or fact. Nevertheless, the Superior Court cannot get involved in the review of any other question of law or fact in the presence of a privative clause. That is the very reason of the enactment of such a clause as the Supreme Court recalls in Control Data. Otherwise the control of the Superior Court extends to all aspects of legality. The Ouellette Report favours on the one hand, the autonomy of Administrative Tribunals; and on the other, it recommends a more extensive control by the Courts... Not easy to reconcile !